2020
DOI: 10.1177/0963689720981878
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Enhanced Apoptosis by Promoting Autophagy Via Akt/mTOR Signaling in Glioma

Abstract: Glioma is the most common malignant tumor in the central nervous system with a poor median survival. Valproic acid (VPA), a widely used antiepileptic drug, has been found to have antitumor effects on gliomas, but its role still has not been determined. In this study, we investigated VPA-induced apoptotic and autophagic effects on human U251 and SNB19 cells by cell counting kit-8 assay, flow cytometry, terminal deoxynucleotidyl transferase-mediated nick end labeling staining, western blots, and immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
(69 reference statements)
1
15
0
Order By: Relevance
“…Since LC3-II is closely associated with the membrane of autophagosomes and p62 is a selective autophagy adaptor/receptor, binding ubiquitinated proteins and LC3 for engulfment, the expression of LC3-II and p62 was examined by Western blot analysis (53). Han et al found that p62 expression was downregulated, while LC3-II expression was obviously upregulated in glioma cells treated with VPA (13). Similar promotion of autophagy could also be seen for Beclin-1 (20).…”
Section: Vpa Was Involved In Cellular Autophagy and Angiogenesismentioning
confidence: 76%
See 4 more Smart Citations
“…Since LC3-II is closely associated with the membrane of autophagosomes and p62 is a selective autophagy adaptor/receptor, binding ubiquitinated proteins and LC3 for engulfment, the expression of LC3-II and p62 was examined by Western blot analysis (53). Han et al found that p62 expression was downregulated, while LC3-II expression was obviously upregulated in glioma cells treated with VPA (13). Similar promotion of autophagy could also be seen for Beclin-1 (20).…”
Section: Vpa Was Involved In Cellular Autophagy and Angiogenesismentioning
confidence: 76%
“…Further functional investigation illustrated that VPA upregulated expression of cleaved caspase 3 and cleaved caspase 9. Moreover, the expression of Bcl-2 family protein Bax and Bak was increased, whereas Bcl-2, Bcl-xl, and Mcl-1, the anti-apoptotic members, were decreased by VPA treatment (13,17). Additionally, the release of cytochrome c from the mitochondria under VPA treatment has also been increased.…”
Section: Vpa-induced Glioma Cell-cycle Arrest and Apoptosismentioning
confidence: 96%
See 3 more Smart Citations